Carbonyl and oxidative stress in patients with breast cancer--is there a relation to the stage of the disease? - Tesarová, P; Kalousová, M; Trnková, B; Soukupová, J; Argalásová, S; Mestek, O; Petruzelka, L; Zima, T (Neoplasma, 2007)
UNLABELLED: Oxidative and carbonyl stress may, on one hand, contribute to the progression of cancer, on the other hand, they may have some antiproliferative effects. We examined serum levels of AGEs (advanced glycation end-products), CML (carboxymethyllysine) and AOPP (advanced oxidation protein products) in 86 patients with breast cancer subdivided based on the clinical stage (TNM classification), histologic grading, expression of hormonal and C-erb B2 receptors and in 14 healthy age-matched women as controls. Breast cancer patients had higher serum concentrations of AGEs (325,581 +/- 66,037 vs. 271,322 +/- 34,826 AU, p < 0.01) even in the early stage of the disease; patients with advanced breast cancer (stage III and IV) had significantly higher both AGEs and AOPP (113.0 +/- 44.9 vs. 78.1 +/- 28.4 micromol/l, p < 0.05) levels, not only compared to controls, but also compared to stages I and II. Serum levels of AOPP were higher in patients having only weakly positive expression of C-erb 2/Her-neu compared to controls and the patients having the highest C-erb2/Her-neu expression. Serum concentrations of AGEs in patients with breast cancer correlated with the age and also with the serum concentration of AOPP. IN CONCLUSION: breast cancer patients had an early increase of AGEs (marker of the carbonyl stress) followed by further increase of AGEs and elevation of AOPP (marker of oxidative stress) in patients with progressive disease. As the clinical significance of these observations is currently uncertain further studies are clearly warranted, especially with respect to their potential therapeutic implications.
Keywords: Lysine; nádory prsu; lysin; Female; oxidační stres; ženské pohlaví; Protein Carbonylation; Oxidative Stress; lidé; staging nádorů; Glycation End Products, Advanced; Breast Neoplasms; studie případů a kontrol; prognóza; Blood Proteins; Receptor, ErbB-2; estrogeny; krevní proteiny; oxidace-redukce; receptor erbB-2; Estrogens; Case-Control Studies; Oxidation-Reduction; karbonylace proteinů; produkty pokročilé glykace; Prognosis; lidé středního věku; Middle Aged; Neoplasm Staging; Humans